The vascular plants endemic in the state of Queretaro. I. Preliminary numerical analysis and definition of areas of concentration of the restricted-range species - Rzedowski, Jerzy; Calderón de Rzedowski, Graciela; Zamudio, Sergio (Instituto de Ecología, A.C., 2012)
The vascular flora of the state of Queretaro is now estimated in somewhat more than 4000 species. 1625 of these (among species and subspecific entities) have been critically treated in 174 published fascicles of the Flora del Bajío y de Regiones Adyacentes. Out of these 1625 taxa, 588 (36.18%) are of wide distribution. Out of the remaining 1037, 709 (43.63%) are only known from Mexico and 328 (20.18%) limit their distribution to Megamexico 1, Megamexico 2 and Megamexico 3; 45 (2.76%) species are endemic to the limits of the state of Queretaro: 26 (1.6%) are only known from the states of Queretaro and Hidalgo. The Sierra Madre Oriental, central Mexico, the Mexican High Plateau and the Volcanic Transversal Belt contribute respectively with 94 (5.78%), 92 (5.66%), 37 (2.27%) and 13 (0.8%) species of distribution restricted to their respective regions of Mexico. The following parts of Querétaro are identified as particularly diverse in species endemic to the state limits: a) the Queretaran part of Sierra Madre Oriental, b) the driest region of the state located in its central part, c) the deep canyon of Moctezuma river, d) the highest part of Zamorano peak.